Accessibility Evaluation of Web Systems for People with Visual Impairments: Findings from a Literature Survey - Souza, Aline; de Souza Filho, José Cezar; Bezerra, Carla; Alves, Victor Anthony; Lima, Lara; Marques, Anna Beatriz; Teixeira Monteiro, Ingrid (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2024)
Accessibility evaluation is essential to determine how accessible a Web system is so that any user can access its content regardless of their limitations. In this context, this work presents a literature survey focused on the accessibility of Web systems, targeting users with visual impairments, emphasizing the importance of including accessibility from the initial phases to the completion of system development. Based on systematic procedures, we seek to provide a current view of the resources available in the technical literature for evaluating Web accessibility, with the primary goal of identifying and bringing together a variety of attributes, methods, metrics, and tools for accessibility improvement of Web systems. We analyzed 1245 papers in the literature; among them, 52 studies demonstrated available resources for evaluating systems by developers. We found that manual evaluation, evaluation with expert users, evaluation with end-users, and heuristic evaluation are the most recurrent accessibility evaluation types. We also cataloged 22 automatic tools, 16 attributes, 15 manual or automatic approaches, and seven heuristics for evaluating accessibility in Web systems. From our findings, it is possible to observe which resources have been used to maintain compliance with accessibility standards, helping professionals to include accessibility in their projects.